THE REGIONAL SPECIFICITIES AND SUSTAINABLE DEVELOPMENT OF RURAL AREAS IN SERBIA - Zakic, Zorka; Stojanovic, Zaklina (Economics of Agriculture, 2006)
The main characteristic of rural policies is the shift from a sectoral to territorial policy approach. It includes attempts to improve co-ordination and to integrate the various sectoral policies at regional and local levels. An increased focus is placed on local specificities as a means of generating new competitive advantages. Another feature of present rural policies is the increased use of partnerships between public, private and voluntary sectors in the development and implementation of local and regional policies. There are clear moves away from centralized «top-down» approach to more local «bottom-up» approach in rural policy application. This kind of policy requires identification each particular areas opportunities and advantages as well as its disadvantages. In Serbia this analysis has to be based on the rural score card definition, which implies that rural areas are not homogeneous, with uniform problems and similar opportunities.